Effects of the ion-beam voltage on the properties of the diamond-like carbon thin film prepared by ion-beam sputtering deposition - 孙鹏 胡明 张锋 季一勤 刘华松 刘丹丹 冷健 (Chinese physics B, 2015)
Diamond-like carbon （DLC） thin film is one of the most widely used optical thin films. The fraction of chemical bondings has a great influence on the properties of the DLC film. In this work, DLC thin films are prepared by ion-beam sputtering deposition in Ar and CH4 mixtures with graphite as the target. The influences of the ion-beam voltage on the surface morphology, chemical structure, mechanical and infrared optical properties of the DLC films are investigated by atomic force microscopy （AFM）, Raman spectroscopy, nanoindentation, and Fourier transform infrared （FTIR） spec- troscopy, respectively. The results show that the surface of the film is uniform and smooth. The film contains sp2 and sp3 hybridized carbon bondings. The film prepared by lower ion beam voltage has a higher sp3 bonding content. It is found that the hardness of DLC films increases with reducing ion-beam voltage, which can be attributed to an increase in the fraction of sp3 carbon bondings in the DLC film. The optical constants can be obtained by the whole infrared optical spectrum fitting with the transmittance spectrum. The refractive index increases with the decrease of the ion-beam voltage, while the extinction coefficient decreases.